Evaluation of the potential of using MEMS accelerometers onto an active vibration control system - Bastos, Ivo Silva (2023)
Active vibration control systems can greatly reduce unwanted vibrations to improve the performance of machines or structures. Bosch Home Comfort Group (Wernau) intends to test the applicability of active vibration control systems in its heat pumps to reduce operating noise. Thus, it is necessary to monitor its mechanical vibrations. Piezoelectric transducers are generally used to measure accelerations on component surfaces, therefore monitoring their vibration levels. However, these types of sensors have a very high cost, which means that active vibration control systems are generally not economically viable. Micro Electric Mechanical Sensor (MEMS) accelerometers have been rapidly evolving, getting close to the performance of typical piezoelectric for certain frequency ranges. Given that their cost is much lower, they emerge as an alternative that could completely change the economic viability of active control systems, which in turn would allow their large-scale application in heat pumps. During the internship, a throughout analysis of several MEMS accelerometers was conducted, under three distinct frequency spectrums, by comparing their performance to reference piezoelectric accelerometer. Initially, a graphical user interface was developed to be used with a shaker testing setup and, on a latter stage, tests were conducted by mounting the accelerometers on Bosch’s heat pump compressor. Results have revealed that MEMS transducers can have a very comparable response to the piezoelectric accelerometers. The BMI323, IIS2DH, and IIS3DWB accelerometers are suitable for integration onto an active vibration control system operating within the 500Hz frequency range. Both the IIS2DH and IIS3DWB have also shown very satisfactory response signals comparatively to the reference transducer in the wider 1kHz range. Notably, the IIS3DWB revealed extended capabilities, demonstrating a reliable performance up to the 5kHz range. Utilising MEMS accelerometers onto an active vibration control system is essential to give this system the necessary economic viability for its largescale implementation in Bosch’s heat pumps. This would greatly improve heat pumps, making them less noise pollutant, and ultimately enhancing the safety and well-being of individuals.